The Role of Wolves in Regulating a Chronic Non-communicable Disease, Osteoarthritis, in Prey Populations - Hoy, Sarah R.; Vucetich, John A.; Peterson, Rolf O. (Frontiers in Ecology and Evolution, 2022)
It is widely accepted that predators disproportionately prey on individuals that are old, weak, sick or injured. By selectively removing “less-abled” individuals, predators may play an important role in regulating the overall health of prey populations. However, that idea is seldom tested empirically. Here we assess the extent that wolves (Canis lupus) select adult moose (Alces alces) in Isle Royale National Park on the basis of age-class and osteoarthritis, a chronic, non-communicable disease. We also assess how temporal variation in kill rates (on moose by wolves) were associated with the subsequent incidence of osteoarthritis in the moose population over a 33-year period (1975-2007). Wolves showed strong selection for senescent moose and tended to avoid prime-aged adults. However, the presence of severe osteoarthritis, but not mild or moderate osteoarthritis, appeared to increase the vulnerability of prime-aged moose to predation. There was weak evidence to suggest that senescent moose with osteoarthritis maybe more vulnerable to wolves, compared to senescent moose without the disease. The incidence of osteoarthritis declined following years with higher kill rates (Fig. 4, Table 1) – which is plausibly due to the selective removal of individuals with osteoarthritis. Together those results suggest that selective predation plays an important role in regulating the health of prey populations. Additionally, because osteoarthritis is influenced by genetic factors, these results highlight how wolf predation may act as a selective force against genes associated with developing severe osteoarthritis as a prime-aged adult. Our findings support giving priority for allowing predation to regulate the health of prey populations. The evidence we present for predation’s influence on the health of prey populations is also relevant for policy-related arguments about refraining from intensively hunting wolf populations.